A triple compound pendulum model to analyse the effect of an ankle-foot orthosis on swing phase kinematics. (February 2023) - Marconi, Grace; Gopalai, Alpha Agape; Chauhan, Sunita
Highlights: A novel triple compound pendulum model is used to identify the effect of orthoses on gait kinematics. Additional mass and actuator positions cause faster and shorter steps on the affected side. Orthosis optimisation based on mass distribution could potentially improve gait rehabilitation. Abstract: Powered ankle-foot orthoses can be utilised to overcome gait abnormalities such as foot drop; however, normal gait is rarely restored with compensatory gait patterns arising and prevalence of gait asymmetry. Therefore, this study aims to determine the effect of orthosis mass and mass distribution on the swing phase of gait, to understand residual gait asymmetry with orthosis use. Using a triple compound pendulum model, which accounts for mass distribution of the limb and orthosis, the swing phase of gait is simulated in terms of natural dynamics and the effect of an orthosis on kinematic parameters is quantitatively determined. It was found that additional mass causes faster and shorter steps on the affected side due to rapid knee extension and reduced hip flexion, with particular actuator positions and natural cadence causing varying severity of these effects. Our study suggests that this model could be used as a preliminary design tool to identify subject specific optimum orthosis mass distribution of a powered ankle-foot orthosis, without the need for motion data or experimental trials. This optimisation intends to more accurately mimic natural swing phase kinematics, consequently allowing for the reduction in severity of gait asymmetry and the potential to improve rehabilitative outcomes.